2013
DOI: 10.1521/aeap.2013.25.5.394
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Delivering Evidence-Based HIV/STI Prevention Programming to a Community Sample of African American Teen Girls Via the Internet

Abstract: The current study examined the feasibility of an HIV/STI prevention intervention for African American female adolescents. The intervention, SiHLEWeb, is a web-based adaptation of the evidence-based intervention, Sistas, Informing, Healing, Living, and Empowering (SiHLE). Participants were 41 African-American girls aged 13 to 18 years, recruited in collaboration with community partners (local high schools, Department of Juvenile Justice, child advocacy center, medical university). Results support the feasibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 29 publications
1
56
0
1
Order By: Relevance
“…Specifically, we sought to determine if a community sample of girls would indeed log onto SiHLE Web and complete its content in their natural environment (e.g., home). Results from the feasibility trial were promising, with 88% logging onto the website at least once and the majority (63.4%) completing the site in its entirety (45). Encouraged by the results of both usability and feasibility testing, next steps in the evaluation of SiHLE Web include larger scale investigation of the effectiveness of the website in preventing HIV risk behaviors through an RCT.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we sought to determine if a community sample of girls would indeed log onto SiHLE Web and complete its content in their natural environment (e.g., home). Results from the feasibility trial were promising, with 88% logging onto the website at least once and the majority (63.4%) completing the site in its entirety (45). Encouraged by the results of both usability and feasibility testing, next steps in the evaluation of SiHLE Web include larger scale investigation of the effectiveness of the website in preventing HIV risk behaviors through an RCT.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, prior research has shown that Internet use is common among HIV-positive persons in the USA (Mayben & Giordano, 2007; Thomas & Shuter, 2010), paralleling trends seen in the broader USA population (Brenner & Smith, 2013). Online interventions have been increasingly used to deliver HIV-related primary prevention (Adam et al, 2011; Bull, Pratte, Whitesell, Rietmeijer, & McFarlane, 2009; Danielson et al, 2013; Hightow-Weidman et al, 2012; Hirshfield et al, 2012; Rhodes et al, 2011; Rosser et al, 2010; Young et al, 2013) and secondary prevention (Horvath et al, 2013; Marhefka et al, 2013; Shegog, Markham, Leonard, Bui, & Paul, 2012) interventions and have focused on providing education, risk reduction skills training, and/or peer support to promote behavior change. However, with one exception (Marhefka et al, 2013), all have targeted either adolescents and/or men who have sex with men.…”
Section: Introductionmentioning
confidence: 99%
“…To complicate matters, women with HIV are disproportionately African American or Latina and overwhelmingly socioeconomically disadvantaged, factors that are associated with lower rates of Internet use (Zickuhr & Smith, 2012). These challenges may, in part, explain why most HIV-related online interventions have been tailored for men who have sex with men (MSM) or adolescents (Bull, Levine, Black, Schmiege, & Santelli, 2012; Danielson et al, 2013; Hightow-Weidman et al, 2012; Hirshfield et al, 2012; Horvath et al, 2013; Rosser et al, 2010; Young et al, 2013). …”
mentioning
confidence: 99%